2020
DOI: 10.1111/jcmm.15387
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle‐enclosed miR‐486‐5p mediates wound healing with adipose‐derived stem cells by promoting angiogenesis

Abstract: Adipose‐derived stem cells (ASC) are said to have a pivotal role in wound healing. Specifically, ASC‐secreted extracellular vesicles (EV) carry diverse cargos such as microRNAs (miRNAs) to participate in the ASC‐based therapies. Considering its effects, we aimed to investigate the role of ASC‐EVs in the cutaneous wound healing accompanied with the study on the specific cargo‐medicated effects on wound healing. Two full‐thickness excisional skin wounds were created on mouse dorsum, and wound healing was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 32 publications
3
68
0
Order By: Relevance
“…This suggests that smooth muscle cells could be the main receptor cells for miR-486 within the AVM context. Recent papers point out a role for miR-486 in the cardiovascular system, including angiogenesis and myocardial infarction [16,17], or even as a biomarker of cardiac pathologies such as bicuspid aortic disease [18]. Thus, we hypothesize that the increase in miR-486 in exosomes might alter the vascular remodeling, contributing to the development of AVM in HHT.…”
Section: Discussionmentioning
confidence: 84%
“…This suggests that smooth muscle cells could be the main receptor cells for miR-486 within the AVM context. Recent papers point out a role for miR-486 in the cardiovascular system, including angiogenesis and myocardial infarction [16,17], or even as a biomarker of cardiac pathologies such as bicuspid aortic disease [18]. Thus, we hypothesize that the increase in miR-486 in exosomes might alter the vascular remodeling, contributing to the development of AVM in HHT.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have also shown an increase of miR-486-5p in patients with coronary artery disease ( Niculescu et al., 2015 ). More recently, miR-486-5p enriched in adipose-derived stem cell–EVs have been shown to accelerate the proliferation of skin fibroblasts ( Lu et al., 2020 ). Furthermore, miR-486-5p was shown to reduce ABCA-1 expression in macrophages ( Liu et al., 2016 ) that we reproduced through our studies of BMDM-HG-exo, which in this context could contribute to atherosclerosis acceleration in Apoe −/− mice treated with BMDM–HG-exo, and atherosclerosis in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-22 could regulate endothelial angiogenesis, in ammation, and tissue injury by targeting vascular endothelial-cadherin [51]. MiR-486-5p released by adipose-derived stem cell-derived EV could mediate wound healing and promote angiogenesis [52]. MiR-21-5p could promote extracellular matrix degradation and angiogenesis in the unilateral anterior crossbite model [53].…”
Section: Discussionmentioning
confidence: 99%